Nutritional value of larvae and pupae of silkworm (Bombyx mori) (Lepidoptera: Bombycidae) - Rodríguez-Ortega, Alejandro; Pino-Moreno, José Manuel; Ángeles-Campos, Sergio Carlos; García-Pérez, Águeda; Barrón-Yánez, Rosario Melina; Callejas-Hernández, Judith (Revista Colombiana de Entomología, 2016)
The objective of this study was to compare the nutritional quality of larvae and pupae of the silkworm (Bombyx mori). A proximal analysis was performed on: energy (kcal/kg), minerals (%), protein (%), and in vitro digestibility of larvae and pupae of Bombyx mori on wet and dry bases. One hundred (100) larvae and 100 pupae produced under laboratory conditions in July and August 2013 were used. Analysis was performed one month after collection in the laboratory of the Department of Animal Nutrition and Biochemistry of the Faculty of Veterinary Medicine of the National Autonomous University of Mexico. According to statistical analysis, on dry bases, the pupae showed higher energy (4231.89 kcal/kg), mineral (6.25%), protein (64.31%), and fat extract (20.63%) content; as compared with larval energy (4115.79 kcal/kg), mineral (5.02%), protein (62.60%), and fat extract (12.90%) content. Silkworm larvae and pupae are ingredients for the production of cattle rations and the preparation of conventional foods that are rich in protein, fat, and minerals.